A N‐Heterocyclic Carbene‐Palladacycle with Constrained Aliphatic Linker: Synthesis, Characterization and Its Catalytic Application towards Suzuki‐Miyaura Cross‐Coupling. Issue 12 (25th October 2021) - Zuo, Bin; Lu, Zeye; Wu, Xiaoqiang; Fang, Weiwei; Li, Wanfang; Huang, Mingxian; Yang, Dong‐Yuan; Deng, Qinyue; Tu, Tao
Abstract: The Suzuki‐Miyaura coupling of various (hetero)aryl chlorides with aryl boronic acids was accomplished by N ‐heterocyclic carbene‐palladacycles (NHC−Pdcycle ) in the aqueous phase. Intriguingly, the NHC−Pdcycle with a constrained aliphatic linker between the NHC ligand and the palladacycle moieties exhibited higher catalytic efficiency than the one without constrained linker under the identical reaction conditions, due to the fixed spatial structure around the metal catalytic center. The present outcome may offer a new strategy for the catalyst design. Abstract : A N ‐heterocyclic carbene‐palladacycle with a constrained aliphatic linker exhibited higher catalytic efficiency than the one with a flexible linker in the Suzuki‐Miyaura coupling reactions of (hetero)aryl chlorides under mild conditions.